Death rate and causes of death in the neonatal intensive care unit in the Children Welfare Teaching Hospital (2018-2021) - Albermany, Sura; Abd Alwahab Mahdi , Noor (Journal of the Faculty of Medicine Baghdad, 2023)
Background: The first month of life is the most vulnerable period and mortality during this period is an important component of under-5 mortalities. Causes of death in this period are preventable like sepsis, RDS, and asphyxia, while others are not like multiple congenital abnormalities.Objectives: To study the death rate and main causes of death in the neonatal intensive care unit (NICU) of the Children Welfare Teaching Hospital (CWTH) through the period (2018-2021).Patients and methods: The death per year for the four years of the study and causes of death were collected retrospectively and analyzed for total death rate and rate for each year, sex distribution, male-to-female ratio, early and late death rate, and main causes of death.Results: it was found that the total death rate is 17.3%, male: female ratio 1.6: 1. The early neonatal death was 54.3% and the late neonatal death was 45.6%. The main causes are congenital anomalies (39%), sepsis (17.4%), prematurity (16.9%), RDS (10.8%), postoperative complications (7.5%), and birth asphyxia (1.9%).Conclusions: The death rate in the NICU / CWTH is still high despite improvement in respiratory care and the use of invasive and noninvasive respiratory support. The death rate because of congenital abnormalities was the main cause of death.Received: Dec,, 2022Accepted: July, 2023Published: Oct.2023